The Influence of Gamification on Improving Students' Listening Skills In Teaching Listening Skill Program - ningtyas, Mega; Astuti, Widi; Aisyah, Aisyah (Program Studi Pendidikan Bahasa Arab of STAI Ali bin Abi Thalib Surabaya, 2024)
This study aims to determine the effect of gamification on improving listening skills in the Teaching Listening Skills Program. This research is quantitative. This study population consists of third-semester students majoring in Arabic Language Education at the Islamic College of Syuhada Mosque Yogyakarta. This research uses data analysis techniques including assumption and hypothesis testing. This study's gamification methods include role-playing, educational games related to listening material, relay message competitions, and interactive oral quizzes. The results indicate that gamification positively affects students' listening skills; however, there is no significant influence between gamification and the improvement of students' listening skills, as the effect is only 0.1%.